Effects of Pilates compared to whole-body vibration on range of motion in postmenopausal women.: A randomized controlled trial: Pilates vs WBV on range of motion - Victória Branco, Larissa; C. Oliveira, Laís; F. Santos, Claudinei; A. A. Pires-Oliveira, Deise; G. Oliveira, Raphael (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Postmenopause is marked by a sudden drop in hormone levels, leading to several physical, psychological, and functional changes. Thus, range of motion (ROM), an important component for maintaining functionality, is also affected. One way to improve ROM is by using the Pilates method, which has already proven effective for this component. Another intervention option is whole-body vibration (WBV), however, little is known about the effectiveness of this therapy in ROM. Objective: To compare the effects of Pilates vs. WBV on ROM in postmenopausal women. Methods: Randomized, single-blind, controlled study with 51 postmenopausal women. Pilates and WBV were performed three times a week for six months, totaling 78 sessions. The control group maintained their usual routine. ROM was assessed in trunk flexion and extension movements using a fleximeter. Results: Post-intervention, no difference (p > 0.05) was observed between Pilates and WBV (trunk flexion: 4.9º [95% CI, -0.4 to 10.2] p=0.247, d=0.62; trunk extension: 1.9º [-0.2 to 4.0] p=0.262, d=0.62). Compared with the control group, only Pilates was significantly superior for trunk flexion (8.8º [95% CI, 3.4 to 14.3] p=0.009, d=1.09) and extension (3.2º [95% CI, 0.8 to 5.6] p=0.024, d=0.90), with a large effect size (d > 0.80). Conclusions: Pilates and WBV did not differ significantly for ROM, either in trunk flexion or extension in postmenopausal women. However, only Pilates was superior to the control group, which maintained the usual routine.